Planning Bibliography Series No. 115 Project Evaluation and Benefit Analysis - Planning Commission (Planning Commission Government of India, 1986)
The document presents a comprehensive bibliography on project evaluation and cost-benefit analysis, compiled by M.K. Jain for the Planning Commission. It catalogs over 70 key works, including books, articles, and indexed periodicals, covering theoretical frameworks, practical applications, and case studies in sectors such as agriculture, infrastructure, and industry. Designed for researchers, policymakers, and practitioners, the bibliography highlights emerging trends, global perspectives, and methodologies relevant to evaluating public and private projects. It serves as an essential resource for informed decision-making and advancing research in project evaluation.
Planning Commission Library New Delhi August 14, 1906
Planning Commission Library New Delhi August, 14, 1906
Keywords: Project Evaluation; Cost-Benefit Analysis; Bibliography; Planning Commission; Economic Assessment; Public Projects; Methodologies; Case Studies; Policy Analysis; Research Insights; Emerging Economies; Decision-Making